Menstrual Cycle as Protective Factor and Increasing Risk Factor of Diabetes Mellitus in Male Persons Proved According to the Ancient Ayurvedic Literature - Reddy, Dr. K. R. C. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: The current demographic definitions for diabetes mellitus have not cited gender nor accounted for the possibility that healthy menstrual cycles may be a protective factor for the development of Type 2/noninsulin-dependent diabetes mellitus. The ancient physician Vallabhacharya posits that the monthly cycle of menstruation rids the blood of toxins that may build up and cause disease and presents this as a reason for less prevalence of Prameha (Madhumeha/diabetes) in women. Aim: The study conducted as a meta-analysis of five clinical studies to observe whether a significant difference in diabetes occurrence exists in menstruating females and similarly-aged males, as well as non-menstruating older females versus 50+ aged males. Materials and Methods: A meta-analysis was conducted with data from a series of clinical studies conducted at the Outpatient Department of SS Hospital, IMS, BHU. The studies were done in conjunction with MD (Ayurveda) and PhD (Ayurveda) studies in the Department of Rasa Shastra, Faculty of Ayurveda, at BHU, Varanasi. Using different Ayurvedic dosage forms, in five different clinical studies, collected data included gender and age group as well as blood sugar levels. Results: The results of each of five studies revealed that the numbers of male patients are more in number. The numbers of females in the study of menstrual age were less than those who had stopped menstruating. Conclusion: The results support the Ayurvedic logic that the menstrual period is an effective physiologic occurrence for regular cleaning of the blood and proposed the male gender as a possible risk factor for diabetes.